Histological Effects of Continuous Prolonged Use of Monosodium Glutamate on Kidneys of Adult Wistar Rats (Journal of Fatima Jinnah Medical University, 2025)
Background: The generous use of MSG in commercial and domestic areas in Pakistan forms the basis of this study. The hypothesis resides on the fact that kidneys are excretory route of nitrogenous waste products; therefore endure most of the harmful effect s of MSG.Methods: The study was done on 45 adult Wister rats randomly divided in three groups. The experimental groups A was given 6 mg/kg body weight of MSG and group B was given 18mg/kg body weight of MSG once daily for 12 weeks duration whereas group C was kept as control. After 12 weeks, kidneys were removed and processed for routine histological examination, integrity of basement membrane was observed by PAS staining technique. The variables recorded include changes in organ weight, relative tissue weight index and changes in structure of uriniferous tubules.Results: The microscopic examination of experimental groups A and B showed changes in renal corpuscles, vacuolization in cells of tubules, sloughing off tubular cells as compared to control groups C as a result of continuous use of MSG. Changes were more marked in Experimental Group B as compared to Group A.Conclusion: Continuous use of MSG in moderate to high doses has a deleterious effect on the nephrons of adult Wister rats. Since, similar changes are expected in human being, a cautious use is advisable. These findings could direct a path for future research in human beings and exploration of preventive measures to minimize the side effects.
Keywords: Monosodium glutamate, Renal corpuscle, Bowman’s space, Uriniferous tubules